LGG-55. OUTCOME OF BRAF V600E PEDIATRIC GLIOMAS TREATED WITH TARGETED BRAF INHIBITION. (4th December 2020) - Nobre, Liana; Zapotocky, Michal; Ramaswamy, Vijay; Ryall, Scott; Bennet, Julie; Alderete, Daniel; Guill, Julia Balaguer; Baroni, Lorena; Bartels, Ute; Bavle, Abhishek; Bornhorst, Miriam; Boue', Daniel R; et al.
Abstract: Children with pediatric gliomas harboring BRAF V600E mutation have a poor outcome with current chemoradiation strategies. Our aim was to study the role of targeted BRAF inhibition in these tumors. We collected clinical, imaging, molecular and outcome information from BRAF V600E glioma patients treated with BRAFi across 29 centers from multiple countries. Sixty-seven patients were treated with BRAFi (56 pediatric low grade gliomas, PLGG and 11 pediatric high grade gliomas, PHGG) for up to 5.6 years. Objective responses were observed in 80% of PLGGs compared to 28% with conventional chemotherapy (p<0.001). These responses were rapid (median, 4 months), and sustained in 86% of tumors up to 5 years while on therapy. PLGG which discontinued BRAFi, 76.5% (13/17) progressed rapidly after discontinuation (median 2.3 months). However, upon re-challenge with BRAFi therapy, 90% achieved an objective response. Poor prognostic factors to conventional therapies, such as concomitant homozygous deletion of CDKN2A, were not associated with a lack of response to BRAFi. In contrast, only 36% of PHGG responded to BRAFi with all but one tumor progressing within 18 months. In PLGG, responses translated to 3-year progression-free survival of 49.6% (95%CI, 35.3% to 69.5%) vs 29.8% (95% CI, 20% to 44.4%) for BRAFi vs chemotherapy respectively (p=0.02). The use of BRAFi results in robust and durable responses while on therapy in BRAF V600E PLGG. Prospective studies are required to determine long-term survival and functional outcomes with BRAFi therapy in childhood gliomas.